2018
DOI: 10.1007/s00267-017-0963-8
|View full text |Cite
|
Sign up to set email alerts
|

Composting of Sewage Sludge with a Simple Aeration Method and its Utilization as a Soil Fertilizer

Abstract: The objective of this study was to examine the feasibility of sewage sludge composting using a simple aeration method. Two consecutive composting trials (run A and run B) using Japanese sludge and woodchips (1:1, v/v) were conducted in cubic boxes (0.45 × 0.45 × 0.45 m) made by plywood at Okayama University. Air was forced up through small holes perforated on two open-ended parallel PVC pipes (ø 16 mm, 0.25 m apart) laid at the base. The results show that compost temperatures were rapidly increased to the peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 39 publications
2
4
0
1
Order By: Relevance
“…Consequently, the woodland utilization of SS resulted in an improvement of the soil properties, such as modifying soil pH, bulk density, and organic matter, and dramatically increasing NO 3 − -N. Specifically, the soil pH and NO 3 − -N were positively correlated with the aboveground biomasses in the understory (r = 0.649, p < 0.05; r = 0.600, p < 0.05, respectively). The amendment of sandy soil fertility also promoted tree height and herbaceous coverage, even though there were no significant relationships with those indicators of soil nutrition (Table 4), which is consistent with previous reports [65,99]. Ferreiro-Domínguez et al [51] also observed the effects of SS application (conversion into TN amount of 50 or 100 kg ha −1 ) on soil chemical properties that resulted in positive impacts on the understory production and tree growth in a P. radiata D. Don plantation.…”
Section: Implications For Relationships Between Soil Properties and P...supporting
confidence: 91%
“…Consequently, the woodland utilization of SS resulted in an improvement of the soil properties, such as modifying soil pH, bulk density, and organic matter, and dramatically increasing NO 3 − -N. Specifically, the soil pH and NO 3 − -N were positively correlated with the aboveground biomasses in the understory (r = 0.649, p < 0.05; r = 0.600, p < 0.05, respectively). The amendment of sandy soil fertility also promoted tree height and herbaceous coverage, even though there were no significant relationships with those indicators of soil nutrition (Table 4), which is consistent with previous reports [65,99]. Ferreiro-Domínguez et al [51] also observed the effects of SS application (conversion into TN amount of 50 or 100 kg ha −1 ) on soil chemical properties that resulted in positive impacts on the understory production and tree growth in a P. radiata D. Don plantation.…”
Section: Implications For Relationships Between Soil Properties and P...supporting
confidence: 91%
“…Crops cultivated using stabilized sewage sludge include the Japanese mustard spinach, Brassica rapa L. var. perviridis (Brassicales: Brassicaceae) in Japan [3]. Sewage sludge can be re-used as fertilizer in forest plantations, degraded area under recovery process and in agriculture, reducing production costs and environmental risks [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Such observations indicate the supported influence of the application of additional organic matter such as sewage sludge for storing carbon in the soil. Other studies show that sewage sludge [3] or compost application on post-mining soils influences the increase of TC in the soil [29]. The study of Singh et al [30] on coal mine soil also indicated an increase in carbon stock with the duration of the reclamation process.…”
Section: Total Carbon Nitrogen Phosphorusmentioning
confidence: 93%